Tactical knowledge is not dependent upon age or biological maturation in young soccer players - Iván Peña Gonzalez; Alejandro Javaloyes; Eduardo Cervelló; Manuel Moya Ramón (Sport TK)
This study examined how chronological age and maturity status may affect tactical knowledge in young soccer players. Decimal age and maturity status of sixty-six U12 to U14 soccer players were calculated. Their tactical knowledge (declarative and procedural) was assessed using the TCTOF questionnaire. Pearson’s correlation analysis was used to assess the relationship between declarative and procedural knowledge with chronological age and maturity status. Statistical differences in the declarative and procedural knowledge were examined according to age, maturity and field position-related groups. Neither the declarative nor the procedural knowledge showed a significant correlation to chronological age or maturity status (p >.05), nor was the declarative and procedural knowledge different between chronological age, maturity status or field position groups. These findings suggest that tactical knowledge is not age-, maturity- or field position-dependent, which has implications in talent identification, player selection and development programs in young soccer academies and clubs.